2015
DOI: 10.2527/jas.2014-8296
|View full text |Cite
|
Sign up to set email alerts
|

Impact of supplemental protein source offered to primiparous heifers during gestation on I. Average daily gain, feed intake, calf birth body weight, and rebreeding in pregnant beef heifers

Abstract: A 3-yr study was conducted to determine the effect of supplemental protein source on ADG, feed intake, calf birth BW, and subsequent pregnancy rate in pregnant beef heifers. Crossbred, Angus-based, AI-pregnant heifers (yr 1, n = 38; yr 2, n = 40; and yr 3, n = 36) were stratified by BW (450 ± 10 kg) and placed in a Calan Broadbent individual feeding system at approximately d 142 of gestation. Following a 25-d adaptation period, an 84-d feeding trial was conducted. Heifers were offered ad libitum grass hay (8 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…Previous studies in cattle during late gestation [ 14 ] have provided evidence that feeding systems during the last third of gestation can alter the subsequent birth weight of the progeny, suggesting that the maternal dietary energy source may affect fetal growth [ 15 ]. Although the maternal intake of protein has also been shown to be an important factor for fetal growth, Summers et al [ 16 ] found no difference in calf birth BW according to the supplementation strategy applied to their mothers. Similarly, no difference was observed for calf birth BW in the present study, probably because throughout the experiment forage presented median quality (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in cattle during late gestation [ 14 ] have provided evidence that feeding systems during the last third of gestation can alter the subsequent birth weight of the progeny, suggesting that the maternal dietary energy source may affect fetal growth [ 15 ]. Although the maternal intake of protein has also been shown to be an important factor for fetal growth, Summers et al [ 16 ] found no difference in calf birth BW according to the supplementation strategy applied to their mothers. Similarly, no difference was observed for calf birth BW in the present study, probably because throughout the experiment forage presented median quality (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al (2007) and Funston et al (2010) reported an increase in heifer adjusted 205-d weaning BW and actual weaning BW, respectively, for heifers born to cows supplemented with a DDGS-based supplement during late gestation. It is likely that the current study failed to report significant differences in calf weaning BW based on maternal treatment exceeding nutrient requirements in all diets, including the control (Summers et al, 2015).…”
Section: Preweaning and Weaning Calf Performancementioning
confidence: 78%
“…Primiparous heifer management has been reported in detail (Summers et al, 2015). In short, each October, pregnant heifers (yr 1, n = 38; yr 2, n = 40; and yr 3, n = 36) were placed in a Calan Broadbent individual feeding system (American Calan; Northwood, NH) and acclimated to the individual feeding bunks for approximately 25 d before the beginning of the feeding trial.…”
Section: Primiparous Heifer Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The birthweight of calves born to Angus cross-bred cows fed 60% of their requirements between 30 and 85 days or between 30 and 140 days of gestation was the same as offspring born to cows fed 100% of requirements but their liver was heavier (Prezotto et al, 2016). Moreover, nutritional supplementation of restricted beef heifers during pregnancy did not increase offspring birthweight nor subsequent performance (Summers et al, 2015) but increased feedlot efficiency and altered carcass characteristics with a tendency for high fat concentrations in the meat of animal born to restricted, non-supplemented heifers (Summers et al, 2015).…”
Section: Undernutritionmentioning
confidence: 80%